Systematic joints in sandstone - Wojtal, Steven F. (Oberlin College Library, 1986)
Closely spaced, planar joints (fractures with no visible offset) cut this thin sandstone layer. The spacing of systematic joints correlates to the thickness of the fractured layer, with close spacing like that seen here indcating that fractured layer was thin. In the upper right corner of the image, more widely spaced joints indicate a thicker fractured layer.